2010
DOI: 10.1182/blood-2009-10-248732
|View full text |Cite
|
Sign up to set email alerts
|

Supernatant of stored platelets causes lung inflammation and coagulopathy in a novel in vivo transfusion model

Abstract: Transfusion-related acute lung injury is suggested to be a "2-hit" event resulting from priming and activation of pulmonary neutrophils. Activation may result from infusion of lysophosphatidylcholines (LysoPCs), which accumulate during storage of blood products. In the present study, we developed a syngeneic in vivo transfusion model to test whether storage of platelet concentrates (PLTs) results in lung injury in healthy rats as well as in a "2-hit" model using lipopolysaccharide-pretreated rats. In addition,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
100
3
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(116 citation statements)
references
References 46 publications
12
100
3
1
Order By: Relevance
“…Therefore, the amount of lysoPCs seems merely to reflect RBC volume. In line with this, we recently showed that aged blood products cause TRALI in rats both in the presence and absence of accumulation of bioactive lipids, 45,46 suggesting that the link between lysoPCs and lung injury is not strong. Taken together, the present results do not indicate that a transfusion policy of fresh blood only is beneficial in reducing TRALI.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Therefore, the amount of lysoPCs seems merely to reflect RBC volume. In line with this, we recently showed that aged blood products cause TRALI in rats both in the presence and absence of accumulation of bioactive lipids, 45,46 suggesting that the link between lysoPCs and lung injury is not strong. Taken together, the present results do not indicate that a transfusion policy of fresh blood only is beneficial in reducing TRALI.…”
Section: Discussionsupporting
confidence: 54%
“…A threshold model has been proposed, 19 in which the presence of a strong "first event" may require only a weak second event before TRALI occurs. [44][45][46] In accordance, in a mouse model of TRALI, the presence of an inflammatory reaction resulted in onset of TRALI after a lower dose of antibodies compared with healthy controls. 47,48 Our data suggest that patients with an expected prolonged time on the cardiopulmonary bypass may benefit from HLA/HNA antibody-free blood products.…”
Section: Discussionmentioning
confidence: 74%
“…37,42 Other groups have also reported effects of components present and accumulating in the supernatant of stored platelets on neutrophil activation both in vitro and in animal models. 2,22,[43][44][45] A recent study showed that longer platelet storage was associated with an increased risk of TRALI in patients. 46 One such biologically active lipid that could be formed during platelet storage, plateletactivating factor, is a good inducer of NET formation in vitro, 29 and other biologically active lipids could be as well.…”
Section: Discussionmentioning
confidence: 99%
“…Washing of RBC units removes proinflammatory activity, including both antibodies and lipids, and ALI may be mitigated in high-risk populations by washing of cellular components. [38][39][40] TRALI secondary to RBC infusion results in a number of reported fatalities, and that number has likely increased with antibody-negative plasma transfusion strategies. [1][2][3][4]41,42 Moreover, removal of the lipophilic compounds may also diminish the clinical effects of stored RBCs especially in the critically ill and in the injured.…”
Section: Discussionmentioning
confidence: 99%